Biomining: an Established and Dynamic Biotechnology - DAVID BARRIE JOHNSON (Microbiology Indonesia, 2012)
â€œBiominingâ€ is generic term to describe the application of living organisms to extract and recover metals from mineral ores and waste materials. Since its inception as a crude technology (â€œdump leachingâ€) for treating â€œrun of mineâ€ rocks and boulders that contained too little copper to be processed by conventional processing, engineering options usedÂ  in biomining have becomeÂ  increasinglyÂ  refined and diverse. Currently, microbiological processing is used to extract both base metals (copper, and to lesser extents nickel and zinc) and precious metals (mostly gold) from ores and mineral concentrates in heaps and stirred-tank bioreactors, as well as in dumps. Recent developmentsÂ  includeÂ  the demonstration, at pilot-scale, ofÂ  indrectÂ  leaching of zincÂ  sulfide concentrates,Â  in which the biological step (regeneration of ferric iron) is carried out independently of abiotic mineral oxidation, andÂ  using microbiologically-mediatedÂ  reductiveÂ  dissolutionÂ  ofÂ  ferricÂ  iron mineralsÂ  toÂ  liberateÂ  nickelÂ  from lateritic ores.